(untitled) (Politeja, 2025)
TWAIL (THIRD WORLD APPROACHES TO INTERNATIONAL LAW) TOWARDS THE “STANDARD OF CIVILIZATION” IN PUBLIC INTERNATIONAL LAW WITH PARTICULAR REFERENCE TO THE AFRICAN PERSPECTIVE The aim of the study is to analyze the position of representatives of the Third World Approaches to International Law (TWAIL) movement to the issue of the “standard of civilization” in public international law. This movement cannot be defined as homogeneous; its heterogeneous and multi-faceted structure reflects the origin of its representatives, who represent researchers expressing their position on public international law from the point of view of Latin America, Africa and Asia after World War II, but divided into historical stages significant for this movement. In this study, the debate within TWAIL was limited to the African perspective and was presented divided into the views of contributionists and critical theorists, which, in the author’s opinion, were considered representative of the examined issue. The study ends with a summary, which indicates demands for changes in the regulations of public international law in relation to the concept of “civilized nations”, which is now considered anachronistic, and which, present in the applicable norms, is still an expression of the undemocratic origins of this law, which has no place in today’s pluralistic world and cannot be understood or justified.